2020
DOI: 10.1108/ijphm-11-2016-0062
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to university-industry collaboration in an academic university department in London, United Kingdom

Abstract: Purpose University-industry collaboration yields numerous advantages resulting in potential benefits in funding research and innovation. Despite the numerous benefits, there are various perceived disadvantages of such collaboration especially in the field of child and adolescent psychiatry in prominent academic institutes in London, UK. The purpose of this study is to explore the perceptions, opinions, beliefs and attitudes of the academics and clinicians in an academic university department towards industry c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Various studies have also provided the evidence of the benefits of UIC. These have been documented in form of: sponsored research which eventually developed into practical application (Mirza et al, 2020); potential financial reward of patents and licences that result from the commercialization of academic research (Caulfield and Ogbogu, 2015); knowledge transfer between universities and industrial firms (especially to compensate for low investment in R&D often found in developing countries) (Garcia et al, 2020); gaining access to research funding (Grimaldi and vonTunzelmann, 2002) and expansion of university networks (Murray, 2002;Mirza et al, 2020) among others. University and industry play crucial role in sustaining national innovation systems.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Various studies have also provided the evidence of the benefits of UIC. These have been documented in form of: sponsored research which eventually developed into practical application (Mirza et al, 2020); potential financial reward of patents and licences that result from the commercialization of academic research (Caulfield and Ogbogu, 2015); knowledge transfer between universities and industrial firms (especially to compensate for low investment in R&D often found in developing countries) (Garcia et al, 2020); gaining access to research funding (Grimaldi and vonTunzelmann, 2002) and expansion of university networks (Murray, 2002;Mirza et al, 2020) among others. University and industry play crucial role in sustaining national innovation systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…University and industry play crucial role in sustaining national innovation systems. Collaboration between university and industry is seeing to be fundamental to aptitudes improvement, generation, obtaining and appropriation of skill, and the advancement of business enterprise (Mirza et al, 2020). In this regard, it has been demonstrated that coordinated effort with university significantly expanded the inclination of industry to present new discoveries and patent.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these barriers have been explored -lack of information on how to access industry, intellectual property issues, university view (poor reputation) of industry collaboration experiences (e.g. financial gain is industry's only interest) (Mirza et al, 2020), cultural differences between organizations including secrecy of industry vs. open dissemination by university academics, lack of trust, and lack of understanding of university norms by industry staff and vice versa (Arenaz & Gonzalez, 2018;Kuwashima, 2018;Meissner et al, 2018). There are also structural barriers which refers to deficiency of TTO in universities as their members lack the required skills to link firms and academia and also the lack of successful entrepreneurial experiences (Siegel et al, 2004).…”
Section: -1 University Industry Collaboration and Its Barriersmentioning
confidence: 99%